PENINGKATAN KAPASITAS KELEMBAGAAN KELOMPOK TANI DALAM PENGEMBANGAN USAHATANI AGROFORESTRY: Studi Kasus di Desa Cukangkawung, Kecamatan Sodonghilir, Kabupaten Tasikmalaya, Provinsi Jawa Barat - Idin Saepudin Ruhimat (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2017)
This study aims to determine the factors that influence the institutional capacity of farmer groups, and to formulate increasing institutional capacity of farmer groups in the agroforestry farming development. Research was conducted in the Cukangkawung Village, Sodonghilir Subdistrict, Tasikmalaya District, West Java Province, from August 2015 to February 2016. Data was analyzed by using Structural Equation Modelling approach (SEM) of SmartPls program. The results showed that (1) the institutional capacity of farmer group was directly influenced by dynamism level and members’ participation and indirectly influenced by role of the leader, capacity of members, extension role, external support, and characteristics of farmers, and (2) efforts to increase institutional capacity of farmer group can be done through increasing dynamism and participation of members in the activities of farmer groups.